FDI and tourism futures: a dynamic investigation for a panel of small island economies. Issue 1 (2nd April 2020) - Fauzel, Sheereen
Abstract : Purpose: Based on a panel vector error correction model (PVECM), this study aims to investigate the impact of foreign direct investment (FDI) on tourism development in a selected group of 17 small island economies during 1995-2018. In the long run, a positive and direct relationship was found between foreign investment and tourists' arrival. Moreover, economic performance and tourists' income were also found to be key determinants of tourism development. It is further observed that there is bidirectional causality between the two variables. Hence, one can argue that FDI is a key element for tourism development. So, if the countries can attract more FDI and grow economically, these elements will contribute positively to the sector in the future. Design/methodology/approach: This work uses rigorous dynamic time series analysis, namely, a dynamic PVECM, which takes into account dynamism and endogeneity issues in tourism modelling. Furthermore, the PVECM is also appropriately suited for integrating short- and long-run analysis. Findings: The results confirm that FDI has been an important ingredient in the tourism development of the island economies in the long run. Interestingly, a bidirectional causality between FDI and tourism development is validated. Moreover, growth will as well be important. So, if the country can attract more FDI and grow economically, these elements will attract the tourists of the future. Originality/value: Relatively few studies have rigorously studied the relationships between FDI and tourism development, particularly with respect to developing countries and small island states which rely heavily on tourism as well as FDI. As such existing research has neglected dynamic and reverse causality analysis in their respective FDI-tourism modelling. This study thus attempts to address the above and supplement the literature by investigating the direct and indirect relationship between FDI and tourism development for the case of small island economies over the period 1995-2018. Moreover, the implication of foreign capital inflows on tourism futures will as well be developed.